Toleransi Dalam Islam (Antara Ideal Dan Realita) - M. Maulana Mas’udi (Al Hikmah, 2019)
AbstractThe tolerance of religious people is a teaching taught in Islam either through the Qur'an or Haditsof the Prophet SAW. In the Qur'an, it is clear that Allah SWT says in surah Al Kafirun verse 6 Surah. 109 : 6 which means : For you your religion and for me my religionIn the hadits narrated that the Prophet SAWever mortgaged his armour to a Jewish person. Equally, the friends, they are very respectful of the non Islamicreligions and tolerate them to implement the teachings of their religions.Similarly, tolerance of religion is still ongoing in Indonesia although its inhabitants have different backgroundseithereducation, economy, tribe, nation, or religion. Muslims have guidance on the Qur'an and As Sunnah, then an obligation for Muslims to implement the Islamic teachings. In particular the majority of the population of Indonesia is Muslim, then the tolerant life style must be applied especially for those who are weak. Do not ever let the dispute moreover the bloodshed among religious people. The author agrees the statement of the former minister of Religious Affairs, Republic of Indonesia, Mr. Mukti Ali, namely : Agree in DifferenceThe life of religious people in Indonesia in reality is in accordance with the teachings of Islam although it has not been as ideal as the existing in the teachings of the Qur'an and Hadits.Keywords : tolerance, ideal, reality